MALE ALLIES OF POLISH WOMEN’S EMANCIPATION. ON THE EXAMPLE OF EDWARD PRĄDZYŃSKI’S AND EUGENIUSZ STARCZEWSKI’S PROJECTS - DUDA, MACIEJ (Society Register, 2021)
This article presents an extract from the research on the male support of the emancipation of Polish women at the turn of the 19th and 20th centuries. In my consideration of the papers penned by authors who posited common and equal civil rights for men and women, I pay particular attention to Edward Prądzyński’s book published in 1873, and to the journalistic writing by Eugeniusz Starczewski from the end of the first World War. Their two projects for the emancipation of Polish women are diverse: while Prądzyński’s proposition was revolutionary, Starczewski’s work was late and limited in its emancipatory outlook.